Pedagogical Strategy In Teaching Autocad: Designing Board Games On Road Safety And Water Conservation By University Students For Kids In Rural Areas - Vasquez-Monteros, Javier; Samaniego-Rojas, Paulo; Celi Sánchez, Carlos Andrés (European Public & Social Innovation Review, 2025)
Introduction: This study investigates an innovative pedagogical methodology for teaching AutoCAD where engineering students design board games on road safety and water conservation for children in rural areas. Methodology: Project-Based Learning (PBL) was applied to students in the "Engineering Drawing" course over two different academic periods. The experimental group (2023) designed board games using AutoCAD, while the control group (2022) followed a traditional methodology. Results: Statistical analyses showed that the grades of the experimental group were lower than those of the control group, but the perception and satisfaction of the experimental group students towards the activity were significantly positive. Discussion: Although grades did not improve, the PBL methodology fostered creativity, collaboration, and social responsibility, highlighting the impact of class schedules on performance. Conclusions: Integrating AutoCAD with PBL in engineering education not only teaches technical skills but also promotes values of social responsibility and ecological awareness, better preparing students for their professional and social futures.